TECHNOLOGIES TO REDUCE EMISSION OF METHANE AND NITROUS OXIDE IN RICE FIELDS: A BRIEF REVIEW - Anicetus Wihardjaka (Agric, 2022)
Climate change caused by increasing anthropogenic greenhouse gas concentrations can threaten food security. Agricultural land is a source of food availability, however it is one source of GHG emissions, especially methane and nitrous oxide. Integration management of land, water, and plants in an integrated manner can be an effort to reduce the impact of climate change. This paper aims to inform the technologies to reduce emissions of methane and nitrous oxide in rice fields. One of the technologies to mitigate greenhouse gas emissions on agricultural land is through the use of natural materials as an inhibitor for the formation of methane and nitrous oxide in the soil due to the content of secondary metabolites in natural ingredients. Natural materials can simultaneously increase nitrogen nutrient uptake and improve crop yields. The methane production in rice fields is suppressed by more than 30% by coconut fiber, turmeric rhizomes, leaf of Ageratum conyzoides, and the leaf of Cosmos caudatus; while application of Cosmos caudatus and Ageratum conyzoides can also reduce the production of nitrous oxide more than 20%, respectively.